SOCS1 expression in cancer cells: potential roles in promoting antitumor immunity - Ilangumaran, Subburaj; Gui, Yirui; Shukla, Akhil; Ramanathan, Sheela (Frontiers in Immunology, 2024)
Suppressor of cytokine signaling 1 (SOCS1) is a potent regulator immune cell responses and a proven tumor suppressor. Inhibition of SOCS1 in T cells can boost antitumor immunity, whereas its loss in tumor cells increases tumor aggressivity. Investigations into the tumor suppression mechanisms so far focussed on tumor cell-intrinsic functions of SOCS1. However, it is possible that SOCS1 expression in tumor cells also regulate antitumor immune responses in a cell-extrinsic manner via direct and indirect mechanisms. Here, we discuss the evidence supporting the latter, and its implications for antitumor immunity.